The Intersection Operation in Light of the Concept of Joint Observables in Fuzzy (Operational) Probability Theory - Taghreed Nasr (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
“Fuzzy probability theory” appeared as a smooth extension of classical probability theory in 1995. It was expected that it will be of great importance in quantum mechanics, but the theory doesn’t keep its development as it was expected. This necessitates revising some of its fundamental basic concepts. We argue that if quantum probability theory should have less constrains than classical probability theory as can be seen in the case of joint random variables, we surely need to weaken the definition of the intersection operation. We will try to discuss the definition validity in quantum probability theory and to discuss the consistency of the given definitions with the whole theory and the possibility to have a more suitable definition.